7n+14=-7+7(5n+7)

Simple and best practice solution for 7n+14=-7+7(5n+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7n+14=-7+7(5n+7) equation:


7n+14=-7+7(5n+7)

We simplify the equation to the form, which is simple to understand
7n+14=-7+7(5n+7)

Reorder the terms in parentheses
7n+14=-7+(+35n+49)

Remove unnecessary parentheses
+7n+14=-7+35n+49

We move all terms containing n to the left and all other terms to the right.
+7n-35n=-7+49-14

We simplify left and right side of the equation.
-28n=+28

We divide both sides of the equation by -28 to get n.
n=-1

See similar equations:

| (4/5)*(3/4) | | -19u=-20u-8 | | -2x-8=44 | | 5/8+7/10= | | -2v-5v=14 | | -6.8-c/1.2 | | -7-7q=-4q-16-12 | | 65+45+y=180 | | 9(-x-2)+4x=42 | | 3(2x+1)=-2(x+5) | | -16t^2+96+8=148 | | -48=2u | | (-4)-(+8)x(-2)-(+15)=-23 | | 3x+8-1x=18 | | (1/21)*(1/31) | | -7-7x+8x=3-4 | | 14p+5[6-(2p+3)]= | | 4+8=13-2r | | 3.2(5x-y)-0.3(-1.6x+7y)= | | -6x=-7x+14 | | -3(4-x)-2=-2(2+x) | | V=(5.5)(3.2)(2) | | -24+x=4(7-3x) | | 2x+7=2x*6 | | 29/24=b+12/b | | 7-6x+x=-18 | | (7/4)*(7) | | -5x+12+12x-3=58 | | 5x-7=-7-29 | | 15(5p-15)=-20 | | 29/24+b+12/b | | sr-t=us+v |

Equations solver categories